What does It Mean to be Ethical in Research? What should It Mean? - Mokhamad Anwar (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2015)
Research Ethics has become one of the most important issues in research activities. Many professional associations, government agencies, and universities have approved specific codes, rules, and policies relating to research ethics. Nuremberg Code 1947 has been a prominent reference for being adopted by organizations in conducting research ethics.This paper tries to explain what research ethics means, how important ethics in research activities, and some ethics principles which many experts shed light on and currently prevail in many organizations including universities. In the end of this paper, it is revealed some of those principles that could be more appropriate to be paid more attention related with the qualitative and quantitative methods employed.